Analisis Pelayanan Personel AMC Dalam Menjaga Keselamatan Penerbangan Sisi Udara Di Bandar Udara Jenderal Ahmad Yani Semarang - Melsy Fransiska Permata Mutiarani; Anita Nur Masyi’ah (Student Research Journal, 2023)
Apron Movement Control (AMC) officers still frequently find plastic, small screws besides bird carcasses, snails, attacks by small birds and other animals. This researcher aims to find out the analysis of AMC personnel services in maintaining flight safety at General Ahmad Yani Airport in Semarang. To find out what obstacles AMC personnel face in maintaining flight safety at General Ahmad Yani Airport in Semarang and how to overcome them. This study uses a qualitative method. The tools used were the researchers themselves, with the results of observations, in the Apron Movement Control (AMC) unit, interviews and documents as supporting documents to answer the formulation of research questions, the researchers conducted a 3-stage analysis consisting of data reduction, data presentation and Conclusion/Verification. The results of this study indicate that 1) The service of Apron Movement Control (AMC) officers has a very important service in ensuring flight security and safety. This can be seen from the Apron Movement Control (AMC) officers at Jenderal Ahmad Yani Airport in Semarang who always carry out their responsibilities by referring to the SOP, before the plane lands or takes off, the AMC officers already check it first. 2) Obstacles faced by Apron Movement Control (AMC) officers. Foreign Object Debris (FOD) was found in the form of aircraft components or other components, machine tools such as small equipment and special equipment, small debris such as sand, loose rock, Small wood, plastic, besides bird carcasses, snails, attacks by small birds and wild animals are Foreign Object Debris (FOD) located at Jenderal Ahmad Yani Airport, Semarang